ANALYSIS OF POWER TRANSFER SYSTEM AND MOVING SYSTEM IN MATIC BUGGY CAR - Samuel Layang; Jhonni Rentas Duling; Airways P Siahan (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2018)
The buggy car is a vehicle possessing mini dimension boarded by single to four passenger seats in which it is able to provide the demand of transportation in industrial estates and plantations such as oil palm plantations. The massive need for a simple transportation to assist the specific human works in the area of plantations in Kalimantan is an appropriate reason to choose this technology. Based these, researchers focus to analyze a simple transportation model, inexpensive, however highly efficient land device for plantation works. This vehicle enormously expected to help the modes of transportation in general plantations and estates. Beside those, it can be an educational model in vocational education of university and college to enhance the student’s interest and skill to deepen the field of educational mechanical engineering. Furthermore the author and team attempt to design then analyze the mechanical drive system and power transmission of Buggy automobile with a simple construction and components that are easily found in the market. This research has conducted by implementing the experimental research type (True Experiment Research). By the results of analyzing the types of actuators, the type of power transmission and steering model for Buggy automobile, it has been obtained that the transmission system used is the CVT (Continually Variable Transmission) type that mechanical works based on engine speed and centrifugal force. Eventually the total weight of buggy car is 157 kg, minimum power at about 5,37 HP, Shaft diameter at around 55 mm, Pitch diameter of Gear spur (dp) integrated in differential gear is 48 mm. The total weight of the vehicle including the weight of the driver has a significant impact on engine performance. Overall, light vehicles must look better because the engine capacity is adjusted to the chassis